The dynamic influence of methane seepage on macrofauna inhabiting authigenic carbonates - Pereira, Olívia Soares (2021)
Methane seeps are highly productive deep-sea ecosystems reliant on chemosynthetic primary production. They are increasingly affected by direct human activities that threaten key ecosystem services. Methane seepage often generates precipitation of authigenic carbonate rocks, which host diverse microbes, and a dynamic invertebrate community. By providing hard substrate, even after seepage ceases, these rocks may promote a long-lasting ecological interaction between seep and background communities. We analyzed community composition, density, and trophic structure of invertebrates on authigenic carbonates at Mound 12, a seep on the Pacific margin of Costa Rica, using one mensurative and two manipulative experiments. We asked whether carbonate macrofaunal communities are able to survive, adapt, and recover from changes in environmental factors (i.e., seepage activity, chemosynthetic production, and food availability), and we hypothesized a key role for seepage activity in defining these communities and responses. Communities on in situ carbonates under different seepage activities showed declining density with increasing distance from the seep and a shift in composition from gastropod dominance in areas of active seepage to more annelids and peracarid crustaceans that are less dependent on chemosynthetic production under lesser seepage. Response to changing environmental context was evident from altered community composition following (1) a natural decline in seepage over successive years, (2) transplanting of carbonates to different seepage conditions for 17 months, and (3) defaunated carbonate deployments under different seepage regimes over 7.4 yr. Seep faunas on transplants to lesser seepage emerge and recover faster than transition fauna (characterized by native seep and background faunas, respectively) and are able to persist by adapting their diets or by retaining their symbiotic bacteria. The macrofaunal community colonizing defaunated carbonates deployed for 7.4 yr developed communities with a similar successional stage as in situ rocks, although trophic structure was not fully recovered. Thus, macrofaunal successional dynamics are affected by habitat complexity and the availability of microbial chemosynthetic productivity. This multi-experiment study highlights the interaction between biotic and abiotic factors at methane seeps at different time scales along a spatial gradient connecting seep and surrounding deep-sea communities and offers insight on the resilience of deep-sea macrofaunal communities.